Colonial Control Through Tangsi Architecture: Moentji in Kazerne Djotangan Surabaya, 1880 - Dilla Sari; Rhoma Dwi Aria Yuliantri; Awanis Alkali (Universitas Hamzanwadi, 2026)
This study aims to examine the mechanisms of bodily control and spatial surveillance of the moentji in Kazerne Djotangan, Surabaya, in 1880. This study uses a historical method with a spatial-architectural analysis of primary sources in the form of the 1880 Distributie plan der Kazerne Djotangan plan from the archives of the Departement van Oorlog (ANRI No. 184). The results of the study indicate that the spatial layout of Kazerne Djotangan does not merely function as a physical structure but as an instrument of power that systematically regulates the bodies and daily lives of indigenous women. The symmetrical placement of barracks around an open field, the lack of adequate private partitions, and the separation of women's wards from military sleeping areas form a surveillance system that operates without the constant presence of guards. The daily rhythm of the moentji is controlled by a military timekeeping system that forces their movements to follow the soldiers' schedules, leaving very little time for personal time. The venereal disease crisis, which peaked in 1880 with 1,013 cases of syphilis among 31,439 troops, prompted the transformation of barracks' medical facilities into apparatuses for the disciplinary actions of the military. Through the health card system and the isolation wards of the Sarnizoeno Infirmario, women, who had previously served as companions to soldiers, were transformed into objects of medical supervision, subject to removal at any time. This study emphasises that colonial power operated not only through formal policies but also through the space, time, and bodies of indigenous women within military institutions.